Development of Try Out Questions for Teacher Professional Education for Teachers in Certain Fields of Study in Fine Arts - iriaji, iriaji; pujiyanto, pujiyanto (STAI Miftahul Ula Nganjuk, 2025)
The development of tryout questions for the Teacher Professional Education in the field of Fine Arts is of high urgency because the quality of the questions greatly determines the participants predicted success in facing the Student Competency Test. This study aims to develop valid and reliable tryout instruments through a Research and Development (R&D) approach with psychometric procedures, including planning, writing, reviewing, and testing 35 questions (25 simple multiple choice and 10 complex multiple choice) to 87 students. Analysis was conducted on the level of difficulty, discrimination power, distractor effectiveness, validity, and reliability. The results showed that the distribution of questions was not ideal, with a dominance of easy questions, few difficult questions, and low discrimination variation. Of the total items, 18 could be used without revision, 9 needed revision, and 8 were discarded. Validity showed that 20 questions were classified as good, while 15 were not yet valid, and the overall reliability of the test was high (? = 0.835). These findings confirm that although the instrument has high reliability, the quality of the items still requires significant revision to meet psychometric standards. Thus, the developed instrument has the potential to be an effective predictive tool for the readiness of Fine Arts students, while also contributing to improving the quality of teacher professional education assessment in Indonesia.